2019
DOI: 10.3389/fpsyt.2019.00882
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Nocturnal Salivary Melatonin Secretion Profiles in Military-Related Posttraumatic Stress Disorder

Abstract: Background: Sleep disturbances are a hallmark of posttraumatic stress disorder (PTSD), yet few studies have evaluated the role of dysregulated endogenous melatonin secretion in this condition. Methods: This study compared the sleep quality and nocturnal salivary melatonin profiles of Canadian Armed Forces (CAF) personnel diagnosed with PTSD, using the Clinician Administered PTSD Scale (CAPS score ≥50), with two healthy CAF control groups; comprising, a “light control” (LC) group with standardized evening light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
0
8
0
1
Order By: Relevance
“…Neuroendocrine PTSD findings consistently demonstrate altered HPA axis reactivity with enhanced negative feedback inhibition and blunted circadian CORT rhythm and CAR, while some studies – but not all – have shown decreased circulating concentrations of CORT (Heim & Nemeroff, 2009 ; Pitman et al, 2012 ; Raison & Miller, 2003 ; Thomas et al, 2012 ; van Liempt et al, 2013 ; Yehuda, 2002 ; Yehuda, Golier, & Kaufman, 2005 ). Interestingly, a recent study showed also blunted nocturnal MLT secretion profiles in military-related PTSD (Paul et al, 2019 ). These findings are similar to many human SD studies, suggesting that the HPA axis- and GC-signalling-specific alterations in PTSD may be partially mediated by sleep and circadian disruption (Chrousos & Kino, 2009 ; Germain et al, 2008 ; Otte et al, 2005 ).…”
Section: Stress and Circadian Dysregulationmentioning
confidence: 98%
“…Neuroendocrine PTSD findings consistently demonstrate altered HPA axis reactivity with enhanced negative feedback inhibition and blunted circadian CORT rhythm and CAR, while some studies – but not all – have shown decreased circulating concentrations of CORT (Heim & Nemeroff, 2009 ; Pitman et al, 2012 ; Raison & Miller, 2003 ; Thomas et al, 2012 ; van Liempt et al, 2013 ; Yehuda, 2002 ; Yehuda, Golier, & Kaufman, 2005 ). Interestingly, a recent study showed also blunted nocturnal MLT secretion profiles in military-related PTSD (Paul et al, 2019 ). These findings are similar to many human SD studies, suggesting that the HPA axis- and GC-signalling-specific alterations in PTSD may be partially mediated by sleep and circadian disruption (Chrousos & Kino, 2009 ; Germain et al, 2008 ; Otte et al, 2005 ).…”
Section: Stress and Circadian Dysregulationmentioning
confidence: 98%
“…However, that correlation was not as strong as in the case with depression. Paul et al [ 59 ], in turn, found a significant reduction in the levels of salivary melatonin at night in soldiers suffering from post-traumatic stress disorder (PTSD). The results published by researchers seem to be very promising.…”
Section: Melatoninmentioning
confidence: 99%
“…Interestingly, in the case of depression, this correlation was much stronger. Moreover, Paul et al showed a significant reduction in the level of melatonin in the saliva of soldiers with post-traumatic stress disorder (PTSD) [ 49 ]. The results released by scientists seem to be extremely propitious; therefore, it is worth expanding the scientific research on melatonin because melatonin in saliva could be a valuable biomarker in the future [ 50 ].…”
Section: Salivarymentioning
confidence: 99%